Effect of dexamethasone in low volume supraclavicular brachial plexus block: A double-blinded randomized clinical study - Arun Kumar Alarasan; Jitendre Agrawal; Bhanu Choudhary; Amrita Melhotra; Satyendre Uike; Arghya Mukherji (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: With the use of ultrasound, a minimal effective volume of 20 ml has been described for supraclavicular brachial plexus block. However achieving a long duration of analgesia with this minimal volume remains a challenge. We aimed to determine the effect of dexamethasone on onset and duration of analgesia in low volume supraclavicular brachial plexus block. Material and Methods: Sixty patients were randomly divided into two groups of 30 each. Group C received saline (2 ml) + 20 ml of 0.5% bupivacaine and Group D received dexamethasone (8 mg) + 20 ml of 0.5% bupivacaine in supraclavicular brachial plexus block. Hemodynamic variables and visual analog scale (VAS) score were noted at regular intervals until 450 min. The onset and duration of sensory and motor block were measured. The incidence of "Halo" around brachial plexus was observed. Student's t-test and Chi-square test were used for statistical analysis. Results: The onset of sensory and motor block was significantly earlier in dexamethasone group (10.36 ± 1.99 and 12 ± 1.64) minutes compared to control group (12.9 ± 2.23 and 18.03 ± 2.41) minutes. The duration of sensory and motor block was significantly prolonged in dexamethasone group (366 ± 28.11 and 337.33 ± 28.75) minutes compared to control group (242.66 ± 26.38 and 213 ± 26.80) minutes. The VAS score was significantly lower in dexamethasone group after 210 min. "Halo" was present around the brachial plexus in all patients in both the groups. Conclusion: Dexamethasone addition significantly increases the duration of analgesia in patients receiving low volume supraclavicular brachial plexus block. No significant side-effects were seen in patients receiving dexamethasone as an adjunct.